A Feasibility study on the expansion of the Posblock Building System - Crisostomo, Catherine Q.; Leung, Vincent Charles P.; Senar, Racquel Theresa S.; Villar, Maria Zenaida P.; Virola, Henry Rophen B. (Diliman, Quezon City College of Engineering, 1992)
In the quest for a cheaper, more efficient alternative means of construction, a formal investigation was undertaken on one such building method: the Posblock Building System. Conducted in five stages, the feasibility study is comprised of a marketing study to determine the Posblock's viability in industry, a technical study to ensure manufacturability and product performance, a financial study to evaluate the project's commercial profitability, an organization and management study for efficient administration, a social profitability study to assess economic and social impacts. The study revealed that a large potential market exists in Manila's middle to lower income classes, as they appreciate cost savings the most. Two key entities proved to be effective vehicles for bringing the Posblock to these brackets: government, since the product fits criteria for low-cost housing; and industry professionals (architects, contractors, engineers) as these play large roles in specifying construction technology to clients. the marketing strategy thus emphasizes the two groups for marketing efforts, complimented by media advertising to reach the general population. Having been produced in the past, Posblock production proves technically feasible by handmold or semi-automated machine. Based on the market potential, the proposed size of production is to be elevated from small to medium scale on the project's onset. Financing through equity and a loan grand from the Department of Science and Technology-Technology Application Promotion Institute (DOST-TAPI) are the proposed means of funding. Based on the projected sales volume for five years, the venture was proved feasible as income is seen in the third year of operations and growing in later ones. Seen to benefit the middle to lower income classes, the Posblock's advantages may eventually be extended to all sectors of society. As a more efficient building system, the Posblock hopes to revolutionize the construction industry's preference for conventional hollow blocks through less material use and wastage, as well as less effort and time in construction. On the economy scale, that's a lot of savings. In a nutshell, yes, the study answered the most basic question : The project is feasible.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Concrete construction industry; Concrete blocks; Participatory monitoring and evaluation (Project management)